2011
DOI: 10.1038/jhh.2011.76
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of differences between repeated pulse wave velocity measurements in terms of ‘bias’ in the extrapolated cardiovascular risk and the classification of aortic stiffness: Is a single PWV measurement enough?

Abstract: Currently, there is no recommendation regarding the minimum number of pulse wave velocity (PWV) measurements to optimize individual's cardiovascular risk (CVR) stratification. The aim of this study was to examine differences between three single consecutive and averaged PWV measurements in terms of the extrapolated CVR and the classification of aortic stiffness as normal. In 60 subjects who referred for CVR assessment, three repeated measurements of blood pressure (BP), heart rate and PWV were performed. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 31 publications
(37 reference statements)
1
20
0
1
Order By: Relevance
“…This should be further investigated. Finally, one should keep in mind that as for BP measurement, standardization of patient conditions and repeated measurements is of utmost importance [1,22,23]. We advise to perform at least two measurements.…”
mentioning
confidence: 99%
“…This should be further investigated. Finally, one should keep in mind that as for BP measurement, standardization of patient conditions and repeated measurements is of utmost importance [1,22,23]. We advise to perform at least two measurements.…”
mentioning
confidence: 99%
“…However, substantial differences in PWV values estimated by different "foot-to-foot" methods have been previously reported (8,22), even when PWV estimates are obtained from Federal Drug Administration-approved commercial apparatuses. Furthermore, it has been observed that a great variability exists among repeated PWV measurements on the same subject with a single device (26).…”
mentioning
confidence: 99%
“…35 For older adults (60-69 years of age), a reference value of cfPWV as 10.3 m/s was derived from an algorithm to convert data obtained from various instrumentation (including the Complior device). 36 Therefore, among our participants of older adults with stroke, the degree to which cfPWV is elevated relative to nonstroke cohorts is greater than the 0.5-m/s difference that is considered to be clinically meaningful 37 and further highlights the multiple issues in the stroke population that affect cardiovascular health and increases their risk for recurrent events.…”
Section: Discussionmentioning
confidence: 89%